A Novel Heat Pulse Method in Determining “Effective” Thermal Properties in Frozen Soil - Wu, Xiao‐long; Zhao, Ying (Water resources research, 2024)
Accurate and fast measurements of thermal properties are frequently required for characterizing the heat‐water dynamics in frozen soil. Measuring the thermal properties of frozen soil without inducing ice thaw has proven challenging with conventional heat pulse (HP) methods. In this study, based on an Infinite Line Source (ILS) semi‐analytical model that applies a constant temperature lower than the freezing point at the heat source to prevent the initiation of ice thaw in the frozen soil, we propose a novel HP‐based approach to measure thermal properties, applicable at temperatures below or above 0°C. Laboratory experiments and numerical modeling were utilized to validate the applicability of the approach and optimization strategies of the measurement. We found that the proposed HP‐based approach effectively maintained the maximum spatial temperature below the freezing point and therefore estimated the bulk thermal properties of quartz sand and ice contents. An optimized measurement strategy was proposed to monitor the temperature variations 2–4 cm away from the center of the heat probe after 60 s. This progress can largely facilitate the determination of the thermal properties of multi‐phase and ‐component frozen soil such as thermal conductivity, heat flux, and ice content in cold areas across soil science, hydrology, engineering, and climate science. Plain Language Summary Frozen soil thermal properties are essential for understanding the potential impacts of varying temperatures on water and heat exchange within the surface soil and the subsurface environment. The conventional method, using the single pulse heating strategy to measure the thermal properties of frozen soil, has difficulty avoiding the ice‐melt process. Ice melt may lead to biased outputs due to the ice melting around the heating probe. In this study, we proposed a novel method to maintain a constant temperature on the heat source surface to avoid the overheating challenge within the measurement. The mathematical model and the proposed workflow can successfully estimate the bulk soil thermal conductivity, heat flux, and soil ice content in cold regions. Key Points A novel approach has been developed using an Infinite Line Source model to predict frozen soil thermal properties and water/ice contents The proposed method offers distinct advantages for measurements, especially in frozen soil with temperatures near the freezing point Further application is valuable regarding its potential merits in minimizing ice melting in the measurement